KERAGAAN LIMA VARIETAS SORGUM (Sorghum bicolor L.) - Ellananggar Agustian; Parwito Parwito; Dia Novita Sari (Fakultas Pertanian Universitas Ratu Samban, 2021)
Sorghum (Sorghum bicolor L.) is a popular alternative plant as raw material for the bioethanol industry. Sorghum plants have the potential to be developed in Indonesia as an alternative resource, new renewable energy raw materials and their stems and leaves can be used as a potential source of animal feed. This research was conducted from February to June 2020. Located in the experimental garden of the Faculty of Agriculture, Ratu Samban Argamakmur University, North Bengkulu Regency, the research objective was to determine the best growth and yield of varieties among the five varieties of sorghum. This research method used a randomized block design (RBD) with one factor, namely, sorghum varieties. Sorghum varieties had a very significant effect on plant height variables of all ages, number of leaves at all ages, leaf width 40 DAS, stem diameter 40 DAS, leaf area 40 DAS, and weight 1000 seeds. In general, the best variety was achieved by the Numbu variety, almost all observations showed that Numbu provided excellent growth in the observation of plant height, leaf length, dry panicle weight and others showed super 2 showed the highest value on stem diameter observations, and kawali on observations. Leaf area and super 1 showed the highest value in the observation of leaf width at the age of 40 days and 45 days after which the highest number was obtained.